On Complete Convergence of Moving Average Process for AANA Sequence - Wenzhi Yang; Xuejun Wang; Nengxiang Ling; Shuhe Hu (Discrete Dynamics in Nature and Society)
We investigate the moving average process such that Xn=∑i=1∞aiYi+n, n≥1, where ∑i=1∞|ai|<∞ and {Yi, 1≤i<∞} is a sequence of asymptotically almost negatively associated (AANA) random variables. The complete convergence, complete moment convergence, and the existence of the moment of supermum of normed partial sums are presented for this moving average process.